ChemInform Abstract: Chiral Ferrocene‐Based P, S Ligands for Ir‐Catalyzed Hydrogenation of Minimally Functionalized Olefins. Scope and Limitations. Issue 39 (September 2016) - Biosca, Maria; Coll, Merce; Lagarde, Florian; Bremond, Emma; Routaboul, Lucie; Manoury, Eric; Pamies, Oscar; Poli, Rinaldo; Dieguez, Montserrat
Abstract: Twelve iridium complexes with planar chiral ferrocenes, e.g. TBSF and DMPF, are prepared and tested as catalysts for the asymmetric hydrogenation of different alkenes.